PENDEKATAN CLASSIC LIFE CYCLE DALAM PERANCANGAN WEB E-COMMERCE UNTUK PENJUALAN PAKAIAN ANIME - Joni Pranta; Nunung Hidayatun (LPPM Universitas Bina Sarana Informatika, 2016)
Abstract - In Indonesia, the typical Japanese animation (anime) favored by many people. Has fans of all ages ranging from children, adolescents and adults. The anime fever makes people look for things that relate to their favorite anime, one of which is clothing with motifs of anime. At least distro or stores that sell clothes anime as well as the limitations of the location as it is only found in a few areas only, making an anime lovers anime difficulty in getting the clothes she wanted. With the web-based sales (e-commerce) can facilitate various parties, the distributions and also the anime lovers. Research Methods and Data Collection Techniques used by the author is a Software Development method which consists of three stages: Needs Analysis, Software Design, Implementation and Testing Unit, for which Data Collection Techniques: Observation and Study Library. Results achieved author that e-commerce website can be created using the programming language PHP and MySQL. Advantages of ordering products on this website save operating costs, promotional costs and labor time compared to booking directly and buyers can view a product category page of this website.Keywords: E-Commerce, Anime ClothingAbstrak - Di Indonesia animasi khas jepang (anime) digemari oleh banyak orang. Memiliki penggemar dari berbagai kalangan usia mulai dari anak-anak, remaja dan orang dewasa. Demam anime tersebut membuat orang mencari hal -hal yang berhubungan dengan anime favoritnya, salah satunya adalah pakaian dengan motif anime. Sedikitnya distro atau toko yang menjual baju-baju anime serta keterbatasan lokasi karena hanya terdapat pada beberapa daerah saja, membuat seorang pecinta anime kesulitan dalam mendapatkan pakai an anime yang diinginkannya. Metode Penelitian dan Teknik Pengumpulan Data yang digunakan penulis adalah Metode Pengembangan Perangkat Lunak dengan pendekatan classic life cycle, dan Teknik Pengumpulan Data yaitu: Pengamatan dan Studi Pustaka. Hasil yang dicapai penulis bahwa website e-commerce dibuat menggunakan bahasa pemrograman PHP dan MySQL. Dengan adanya penjualan berbasis web (e-commerce) dapat menguntungkan berbagai pihak, pihak distro dan juga pihak pecinta anime.